Twitter User Sentiment Analysis on the Mysterious Hepatitis Issue Rstudio - Muhammad Khahfi Zuhanda; Desniarti Desniarti; Muhammad Hafiz (JOURNAL OF INFORMATICS AND TELECOMMUNICATION ENGINEERING, 2022)
In the past few years, Corona Virus Disease 2019 has become the most psychologically disturbing issue for Indonesian people since they first entered Indonesia in early 2020. After starting to subside in 2022, there is now a new issue, namely Mysterious Hepatitis, a frightening specter for parents. This mysterious hepatitis attacks many children and causes death. Social media is a source of Big Data. Media such as Twitter have been used to collect and analyze user data for several different purposes. Data can be used to analyze people's opinions on specific topics and incidents by applying sentiment analysis. Certain helpful information can be extracted from the analyzed data. The purpose of this study is to explore public or netizen opinions regarding mysterious hepatitis via data from netizens' tweets on Twitter. The method used in this research is to collect tweets, then clean the tweets, and finally analyze the data that has been processed via RStudio. The results of this study provide information that the words that often appear are acute, child, case, and health. From bigrams, related words often appear acute hepatitis, mysterious hepatitis, acute mysterious, children, and covid 19. By analyzing the type of emotion using the NRC Word-Emotion Association Lexicon method, Twitter users also provide various emotions related to the #HepatitisMysterius issue, including eight positive emotional responses and six positive emotional responses. “Fear” was the most frequent emotion followed by “anticipation”, “trust”, “surprise”, “anger”, “disgust”, “sadness” and “joy”. From the results of this study, it also informs the advice to be careful with this mysterious hepatitis, because there is advice on being alert for hepatitis and taking care of your health